2005
DOI: 10.1007/s10029-004-0310-x
|View full text |Cite
|
Sign up to set email alerts
|

Discordance between the patient’s and surgeon’s perception of complications following hernia surgery

Abstract: In general, the concordance was poor. These results emphasise the importance of providing detailed information about the usual postoperative course prior to the operation. Whereas the surgeon, from a professional point of view, has a better idea about what should be expected in the postoperative period and how any complications should be categorised, only the patient has a complete picture of the symptoms and adverse events. This makes it impossible to reach complete agreement between the patient's and surgeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 19 publications
2
29
0
3
Order By: Relevance
“…75 The correlation between surgeon and patient opinions of operative outcomes is poor. 36,65 Our results indicate that retrospective reviews underestimate the incidence of complications in spine surgery. Overall, prospective studies reported a higher incidence of complications (19.9%) than did retrospective studies (16.1%, p < 0.0001, OR 1.3).…”
Section: Relevance Of Study Designmentioning
confidence: 77%
“…75 The correlation between surgeon and patient opinions of operative outcomes is poor. 36,65 Our results indicate that retrospective reviews underestimate the incidence of complications in spine surgery. Overall, prospective studies reported a higher incidence of complications (19.9%) than did retrospective studies (16.1%, p < 0.0001, OR 1.3).…”
Section: Relevance Of Study Designmentioning
confidence: 77%
“…18 The accuracy of patient reports of medical complications has not been investigated as thoroughly among surgical patients. Existing studies have been limited to either a single type of surgery 1921 or to a single postoperative complication. 2224 Additional characterization of PROs in a diverse surgical population is necessary if they are to be used to identify postoperative complications for clinical care, for research, or for quality improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Algunos analizan los factores que influyen en el retorno del paciente a las actividades diarias después de una cirugía herniaria 4,7 , otros investigan el rol de la inguinodinia en la satisfacción del paciente con su cirugía 6,9,[17][18][19] . El cuestionario genérico de salud abreviado (SF-36) es frecuentemente empleado en muchos estudios 1,4,8 y también se han aplicado simples cuestionarios indagando la satisfacción subjetiva del paciente con su cirugía 10,20 . Tomando en cuenta estas experiencias desarrollamos el ICCRHL 2,3 , el cual considera los conceptos de la Calidad de Vida Relacionada con la Salud y evalúa mediante preguntas simples la percepción subjetiva del paciente respecto a su cirugía y los resultados objetivos de la misma.…”
Section: Discussionunclassified
“…La satisfacción subjetiva del paciente con su cirugía, evaluada por la pregunta 6, demuestra que la insatisfacción del paciente en los primeros meses después de la cirugía se debe a las complicaciones sufridas en el postoperatorio; a pesar de que desde el punto de vista del cirujano estas complicaciones pueden considerarse como relativamente menores, para el paciente son una causa importante de ansiedad y consiguiente insatisfacción 20 . El incremento de pacientes insatisfechos en el control del primer año y de los 2 años se debe al desarrollo de inguinodinia, la cual constituye una causa importante de insatisfacción con la cirugía [17][18][19][20] .…”
Section: Discussionunclassified
See 1 more Smart Citation